Dealing with microscopic peritoneal metastases of epithelial ovarian cancer. A surgical challenge. (March 2017) - Azaïs, Henri; Estevez, Juan Pablo; Foucher, Périne; Kerbage, Yohan; Mordon, Serge; Collinet, Pierre
Abstract: Understanding biology and progression mechanisms of peritoneal metastases of epithelial ovarian cancer (EOC) is a cornerstone in the knowledge and the comprehensive management of the disease. Despite clinical remission after the association of complete cytoreductive surgery and platinum-based chemotherapy, peritoneal recurrence still occurs in 60% of patients. Eligible studies, published from 1980 to June 2016, were retrieved through ClinicalTrials.gov, MEDLINE, Cochrane databases and bibliography searches. We reviewed all publications that deals with microscopic peritoneal metastases of EOC in French and English. To discuss expected benefits of intraperitoneal (IP) chemotherapy, fluorescence-guided surgery or IP photodynamic therapy, we reviewed most recent and relevant studies. The final reference list was generated on the basis of originality and relevance to the broad scope of this review. Published data concerning early-stage ovarian cancer suggest that occult peritoneal or epiploic metastases are present in 1.2%–15.1% of cases. In the frequent case of advanced-stage disease, residual microscopic lesions are ignored by conventional surgery. We are convinced that microscopic peritoneal metastases are a relevant surgical therapeutic target. This article discusses existing data on microscopic peritoneal metastases, the treatment indications, the diagnostic and therapeutic surgical approaches to be developed and their expected benefits. A local therapeutic strategy to target microscopic lesions is needed in addition to complete macroscopic cytoreductive surgery to decrease the rate of peritoneal recurrence. Intraperitoneal chemotherapy, and targeted photodynamic therapy could play a role in this new paradigm. The roles of these different options must be defined by future researches. Highlights: Peritoneal recurrence occurs in 60% of patients with ovarian cancer after complete macroscopic cytoreductive surgery. Microscopic metastases that are not eradicated by surgery may be one of the mechanisms leading to peritoneal recurrence. Microscopic peritoneal or epiploic metastases are present in 1.2% to 15.1% of early-stage ovarian cancer. Intraperitoneal chemotherapy or targeted photodynamic therapy may play a role in the management of microscopic metastases.